Prediction of Black Soldier Fly Larva Sales and Production Using Linear Regression Method - Saputra, I Made Arya Budhi; Juniawan, Kadek Ardi; Januhari, Ni Nyoman Utami; Gautama, I Made Bhaskara; Sari, Ni Made Wirastika; Arsa, I Gusti Ngurah Wikranta; Wijaya, IGKG. Puritan (Paradigma - Jurnal Komputer dan Informatika, 2023)
The waste problem is a problem that plagues the world. Various programs and methods have been carried out in processing waste. Until now, Bali has become the area with the most waste production in Indonesia, where every day the waste produced reaches 4,281 tons or in other words 1.5 million tons per year. In early 2021, a campaign on the separation of organic and non-organic waste has been initiated in several districts/cities in the province of Bali. The next problem is that people do not know how to process organic waste other than being compost for plants. Black Soldier Fly (BSF) or black soldier fly is an order of diptera whose physical characteristics are similar to wasps. BSF itself has an average life cycle from egg to adult of 45 days. Where the main consumption of BSF itself is organic waste. In Pelaga village, Petang sub-district, Badung district, there is an effort to breed BSF. Where in this effort, it can produce no less than 100 kg of BSF larvae within 15-20 days. The problems encountered by these entrepreneurs are often difficult to predict the amount of BSF larvae production, because around the area there are quite a lot of catfish and chicken farmers who need BSF larvae as feed. The use of linear regression method can overcome these problems. The results obtained between the application of this method include the accuracy value which reaches 62.5% for prediction of sales and 32.5% for prediction of production.